A researcher and activist in the Mexican borderlands. - Deborah W. Kilgore (Adult Education Research Conference, 1997)
Dual roles of activist and researcher in a collective social movement highlight conflicting research needs for objectivity and subjectivity that may be reconciled through self-conscious critique. This was demonstrated during a study of a collective workers' rights movement on the U.S.-Mexico border in 1996.